Management of Central Venous Access in Children With Intestinal Failure: A Position Paper From the NASPGHAN Intestinal Rehabilitation Special Interest Group. Issue 3 (31st March 2021) - Wendel, Danielle; Mezoff, Ethan A.; Raghu, Vikram K.; Kinberg, Sivan; Soden, Jason; Avitzur, Yaron; Rudolph, Jeffrey A.; Gniadek, Michelle; Cohran, Valeria C.; Venick, Robert S.; Cole, Conrad R.
Abstract : Supplemental Digital Content is available in the text Abstract : ABSTRACT: Intestinal failure requires the placement and maintenance of a long-term central venous catheter for the provision of fluids and/or nutrients. Complications associated with this access contribute to significant morbidity and mortality, while the loss of access is an increasingly common reason for intestinal transplant referral. As more emphasis has been placed on the prevention of central line-associated bloodstream infections and new technologies have developed, care for central lines has improved; however, because care has evolved independently in local centers, care of central venous access varies significantly in this vulnerable population. The present position paper from the Intestinal Failure Special Interest Group of the North American Society for Pediatric Gastroenterology, Hepatology, and Nutrition (NASPGHAN) reviews current evidence and provides recommendations for central line management in children with intestinal failure.